Evaluation of native strains of Verticillium lecanii (Zímm.) Viegas in the control of the greenhouse whitefly Trialeurodes vaporariorum (Westwood) - GARCÍA-GONZÁLEZ, JAVIER; LÓPEZ-AVILA, A. (Revista Colombiana de Entomología, 1997)
The greenhouse whitefly Trialeurodes vaporariorum (Homoptera: Aleyrodidae) is an insect pest with a wide range of host plants and causes rever damages and significant losses in field and greenhouse crops such as bean, green bean, pea, and tomato. This study was conducted in order to evaluate the virulence of several native strains of Verticillium lecanii to the greenhouse whitefly and select the most efficient for an Integrated Pest Management program. The median lethal concentration (LC50) of native strains was determined under greenhouse conditions and the enthomopathogenic activity of the selected strains presented as two preformulations were evaluated under field conditions. The greenhouse trials were carried out over nymphs of II instar, testing six native isolates. Among these strains, C17 and C26 were selected in a preliminary assay and their LC50 were determinate. C26 presented a smaller value of LC50 than C17 strain, this value was expressed as propagules/ml. A mass production and formulation process was performed with the strain, C26, obtaining two products: "Wet Powder" and "Freeze-Dried" formulations. These products were tested against the pest in field trials. The "Wet Powder" and "FreezeDried" treatments, infected equal or highest levels of whitefly nymphs, compared with the other treatments, nevertheless there was no significant difference among them.